Pengaruh Work Overload dan Role conflict Terhadap Kinerja Melalui Kepuasan Kerja Karyawan Garuda Lounge Denpasar - Dinda Ferdina, Ni Made; Sedana Putra P, Komang Widhya (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the influence of Work Overload and Role conflict on employee performance with job satisfaction as a mediating variable at the Garuda Executive Lounge Denpasar. The research is grounded in the increasing operational demands within premium service environments, which potentially generate excessive workload and unclear role expectations, thereby reducing job satisfaction and employee performance. The theoretical framework encompasses the concepts of Work Overload, Role conflict, job satisfaction, and employee performance, described through perspectives in human resource management and organizational behavior theory. This research employs a quantitative approach using a survey method with a saturated sampling technique involving 34 employees. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression and mediation testing. The results indicate that Work Overload and Role conflict have a negative and significant effect on job satisfaction, and both variables significantly influence employee performance. Job satisfaction has a positive effect on performance and functions as a mediating variable in the relationship between Work Overload and Role conflict with employee performance. These findings highlight the importance of managing workload distribution and clarifying role expectations to maintain job satisfaction and performance quality within premium service operations.